Kajian Yuridis Kewenangan Tata Kelola Keuangan Badan Pengelola Dana Lingkungan Hidup dalam Proyek Mangrove for Coastal Resilience (M4CR) di Indonesia - Rio Ananda Andriana (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Mangrove forests are crucial coastal ecosystems that play an important role in enhancing the resilience of coastal communities. Indonesia has the largest mangrove ecosystem in the world, covering an area of 3,489,140 hectares. However, unfortunately, this ecosystem is continuously being degraded due to various exploitative and destructive activities. In response to this, in 2020, the Indonesian government launched the Mangrove for Coastal Resilience Program (M4CR) to restore 600,000 hectares of damaged mangrove forests. This program is being implemented by several agencies, such as the Ministry of Finance, the Ministry of Environment and Forestry, Peatland and Mangrove Restoration Agency of the Republic of Indonesia, and the Indonesian Environment Fund (BPDLH). The program is funded through a grant from the World Bank amounting to USD 419 million or IDR 6.5 trillion. The BPDLH plays a crucial role in managing the funds for the M4CR project to ensure proper financial governance and allocation to strengthen coastal areas through mangrove rehabilitation. This article examines the financial governance authority of the BPDLH within the M4CR project through normative legal research and library studies. The findings of this research highlight the authority and limitations of the BPDLH in managing the project funds..